2016
DOI: 10.23887/jpi-undiksha.v5i2.8559
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pembelajaran Inkuiri Terbimbing Berbasis Permainan Dalam Meningkatkan Kreativitas Anak Usia Dini

Abstract: Penerapan pembelajaran pada anak usia dini saat ini masih cenderung menggunakan metode pembelajaran konvensional seperti ceramah. Hal ini mengakibatkan rendahnya perkembangan kreativitas anak. Sehingga dibutuhkan suatu cara dalam meningkatkan kreativitas anak usia dini. Penelitian ini bertujuan untuk mengetahui pengimplementasian metode pembelajaran inkuiri terbimbing berbasis permainan dalam meningkatkan kreativitas anak usia dini. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan menggunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
6
0
9
Order By: Relevance
“…The formulation of the right learning objectives makes it easier to recognize the development of children in various aspects of development. The results of the study showed if the strategies or methods used appropriately in developing parts of child development, then the learning outcomes achieved will be optimal (Laily et al, 2019;Sukmady, 2017;Suryaningsih et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The formulation of the right learning objectives makes it easier to recognize the development of children in various aspects of development. The results of the study showed if the strategies or methods used appropriately in developing parts of child development, then the learning outcomes achieved will be optimal (Laily et al, 2019;Sukmady, 2017;Suryaningsih et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Early childhood development in various aspects, namely the moral aspects of religion, social-emotional, cognitive, motor, physical, language, art and development in the golden period in the stages of life, can determine the subsequent development (Astuti et al, 2020;Fakhriyani, 2016;Mayasari & Ardhana, 2018). One of them is the development of moral values of religion, social, emotional, language, motor physics and art, where aspects of development include language skills, symbolic thinking, being able to move limbs, praying following the religion, diligently helping and working together, exploring and expressing themselves, imagining with movements, music, drama, and various other areas of development (painting development, visual development, craft), and being able to appreciate developmental works (Laily et al, 2019;Sukmady, 2017;Suryaningsih et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, teachers need to develop learning models that can potentially improve students' creative thinking skills. Some learning models that have the potential to develop students' creative thinking skills include STEM learning models (Ismayani, 2016), learning models with group investigation (Christina & Kristin, 2016), guided inquiry learning models (Suryaningsih, Cahaya, & Poerwati, 2016), project-based learning models (Titu, 2015), and the use of realistic mathematics learning (Wijayanti, 2016).…”
Section: Results and Discussmentioning
confidence: 99%
“…Lingkungan sebagai temapat berinterkasi dapat mendukung berkembangnya kreativitas, tetapi ada juga yang menghambat berkembangnya kreativitas individu (Prameswara, 2018). Berdasarkan karakteristik anak dan dunianya dapat diketahui bahwa perkembangan anak serta dalam mengembangkan pemahaman dan kreativitas anak masih membutuhkan bantuan-bantuan dari guru (Made Ayu Suryaningsih et al, 2011). Salah satu cara untuk meningkatkan kreativitas siswa dapat dilakukan dengan cara memilih metode atau pendekatan yang sesuai dengan karakteristik mata pelajaran (Alamsyah, 2016).…”
Section: Penerapan Media Pembelajaran Berbasis Macromedia Flash Dalam...unclassified